VISCERAL MANIFESTATIONS UNDIFFERENTIATED CONNECTIVE TISSUE DYSPLASIA IN PATIENTS WITH CHOLELITHIASIS - S. E. Gumenyuk; R. A. Batchaeva; A. G. Grigoryev; P. G. Storozhuk; V. A. Avakimyan; A. G. Pokhotko; А. M. Manuylov (Кубанский научный медицинский вестник)
The study included 132 patients with cholelithiasis (108 women and 24 men) aged 29 to 77 years. Mean age of patients 53,9 ± 12,8 years. In 63 (47,7%) patients with cholelithiasis clinical signs undifferentiated connective tissue dysplasia of varying severity. Of these, 34% of patients detected abnormality of the gastrointestinal tract. In 26,9% of patients with cholelithiasis diagnosed NDCTD anomalies identified various shapes and positions of the gallbladder.